Pelatihan Pembuatan Media Pembelajaran Berbasis Komputer Di Sekolah Menengah Pertama Kecamatan Rantau Badauh Barito Kuala - Hendrawan, Ahmad; Adawiyah, Rabiatul; Effendi, M Syafwansyah; Arifin, M Khafidz (Jurnal IMPACT: Implementation and Action, 2019)
Rantau Badauh Subdistrict is located in Barito Kuala Regency which is located around 25 km from the capital of Barito Kuala Regency and around 20 km from the Capital City of South Kalimantan (Banjarmasin). The village area consists of paddy fields, yards, swamps, rivers, and forests. Teachers as the spearhead in the world of education, are required to always be responsive and sensitive to the various innovations that occur around them, teachers must be able to follow the rapid development of science, technology and information. Most teachers have not used computer technology for the learning process, for example to create simple computer-based learning media or to administer learning activities. Training activities are carried out using survey methods, lectures, training practices and discussion - consultation. The survey was conducted by distributing a 'user need assessment' questionnaire to school teachers to get the data of the type and needs of teachers in mastering the most needed computer skills. Mastery of computer skills is categorized in supporting the learning process, making learning media. The output target of this activity is to Improve the Teacher's Ability in Developing Computer Based Learning Media. Keywords: Teacher, Learning Media, Computer Based